The Impact of Anxiety on Self-Esteem in a Religious Educational Environment - Brenda Aulia Astrica; Sadam Fajar Shodiq (Journal An-Nafs: Kajian Penelitian Psikologi, 2024)
Self-esteem is a crucial element of self-concept that impacts motivation, morale, and overall quality of life. The school environment plays a crucial role in an individual's self-esteem. The objective of this study is to examine the impact of anxiety on the self-esteem of students in a religious education setting. This study employs a descriptive quantitative methodology, utilizing a sample size of 305 individuals from various religious education institutes selected by random sampling technique. The data collection involved an online questionnaire distributed via Google Forms and analysis utilizing SmartPLS software for structural equation modeling (SEM). The findings of this study suggest that anxiety substantially influences students' self-esteem. These findings highlight the need to establish a favorable educational atmosphere by providing teacher support, fostering positive peer relationships, and maintaining a balanced academic workload as practical approaches to enhance students' self-esteem and alleviate anxiety in a religious education setting.